Study of stressors among undergraduate medical students of a teaching medical institution - Patil, Subita P.; Sadhanala, Snehashree; Srivastav, Manissha U.; BansodeGokhe, Seema S. (International Journal Of Community Medicine And Public Health, 2017)
Background: Stress is a response by which we perceive and cope with environmental threats and challenges. Personal and environmental events that cause stress are known as stressors. Medical students undergo tremendous stress throughout their education. The same stressors may be perceived differently by different medical students, depending on their cultural background, personal traits, experience and coping skills. Inability to cope with the stress may affect their physical and mental well-being. The objectives of the study were to find out stressors among the medical students and study their socio-demographic variables. Methods: A cross-sectional study was conducted amongst 205 undergraduate medical students of III and VII semester posted in the department during August 2016 to January 2017 with a pre- designed, pre-tested, semi-structured questionnaire which consisted of 2 parts: socio-demographic details and MSSQ-20 (medical student stressor questionnaire) after taking their informed consent and Institutional Ethical Committee approval. Results: Out of 205 students, 120 were males and 85 females with a mean age of 20.31±1.74 years. MSSQ-20 analysis revealed that academics, social related, group activities, were the major stressors in the descending order of occurrence. Some of the ways of relieving stress were listening to music, sharing with friends, physical activities etc. Conclusions: Although academic domain was the major stressor, its levels were only moderate due to the student friendly atmosphere at college.